THE EFFECT OF TAX INCENTIVES AND FINANCIAL DISTRESS ON ACCOUNTING CONSERVATISM - Fitriyah; Desi Jelanti (Transpublika Publisher, 2023)
Accounting conservatism is employed to mitigate risk and curb excessive optimism among managers and company owners. However, an excessive application of conservatism may lead to inaccuracies in calculating a company's periodic profit or loss, potentially misrepresenting the company's true financial condition. This study aims to analyze the impact of tax incentives and financial distress on accounting conservatism. The study population comprises food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period from 2016 to 2020. Data for this research were collected from 10 companies that met the sample criteria, resulting in a total of 50 research observations over the 5-year period. The study relies on secondary data and employs multiple linear regression analysis to analyze the data. The findings suggest that (1) tax incentives (X1) have a significant influence on accounting conservatism (Y); (2) financial distress (X2) does not have a significant impact on accounting conservatism (Y); and (3) when considered together, tax incentives (X1) and financial distress (X2) collectively influence accounting conservatism (Y).